The Consequences of the "Missing Girls" of China - Ebenstein, Avraham Y.; Sharygin, Ethan Jennings (World Bank, 2012)
In the wake of the one-child policy of 1979, China experienced an unprecedented rise in the sex ratio at birth (ratio of male to female births). In cohorts born between 1980 and 2000, there were 22 million more men than women. Some 10.4 percent of these additional men will fail to marry, based on simulations presented here that assess how different scenarios for the sex ratio at birth affect the probability of failure to marry in 21st century China. Three consequences of the high sex ratio and large numbers of unmarried men are discussed: the prevalence of prostitution and sexually transmitted infections, the economic and physical well-being of men who fail to marry, and China's ability to care for its elderly, with a particular focus on elderly males who fail to marry. Several policy options are suggested that could mitigate the negative consequences of the demographic squeeze.